Domestic Violence Subjected to Legal and Cultural Pressure - Boujarian, Nazanin; Ninggal, Mohd Tajuddin; Ssekamanya, Siraje Abdallah (2016)
A society based on patriarchal structure brings lots of discriminations against females in family and society, so different violent relationships appear mainly targeting women as the victims. The domestic violence imposed by the partner of the woman tortures her verbally and physically, captures her to live in a suffering environment or enforces her to leave the original city/country and accepts the condition of being a refugee with all of its risks. In order to reduce the immigration troubles, it is important to consider the origins of violence causing these conditions. There are different sources of domestic violence including cultural, social and legal factors. In this study, three important factors are considered as early-child marriage, gender inequality and insufficient legal and protective systems. In child marriage, the girl undergoes a marital status under her father’s pressure. Gender inequalities increase the rate of violence against women, because they have lower financial, educational and social positions and have to be more dependent on their partners. On the other hand, insufficient protective systems constrain women providing conditions to develop domestic violence. Conducting interview sessions with victims of violence, the abovementioned cases are considered and the data analyzed using a qualitative approach. The output of this study helps counselors in healing process of the victims, highlights the necessity of improving skills for controlling violence and notices the importance of modification of supportive legal systems to prevent committing violence against women. So people are encouraged to make a free-violence society based on human values